Analisis Bibliometrik Pada Kecurangan Laporan Keuangan: Publikasi Tiga Dekade Terakhir - Luthfiyyah, Alya; Rachmat Agus Santoso; Fitriana (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2024)
Purpose of the research is to determine the growth of research publications regarding fraud in financial reporting by examining bibliometric analysis from the Scopus database from 1993 to 2022. This research method uses a bibliometric analysis approach. The application system for data visualization uses VOSviewer and Microsoft Excel to perform data frequency analysis. The results of this research indicate that the issue of financial statement fraud is a topic that continues to attract the attention of researchers. Authors contribute to the literature by analyzing publications and authors by year, country, journal, author, and organization. This research can help increase the understanding of other researchers to plan future research to detect and prevent financial statement fraud for the sustainability of an organization. The author tries to conduct a comprehensive review of research on financial statement fraud conducted over three decades. This study makes a significant contribution and provides new insights into financial statement fraud.